A Bibliometric Study of Business Model Innovation Literature - Loso Judijanto (Westscience Press, 2025)
This study presents a comprehensive bibliometric analysis of the global literature on Business Model Innovation (BMI), aiming to uncover its intellectual structure, thematic evolution, and collaborative research patterns. Utilizing data from the Scopus database and visualization tools such as VOSviewer, the study analyzes key co-citation networks, author collaborations, keyword co-occurrences, and temporal publication trends. The findings reveal that BMI has developed around several foundational scholars—most notably Zott, Osterwalder, Chesbrough, and Teece—while branching into emerging research areas such as digital transformation, sustainability, and circular economy. Geographically, the field is led by countries such as China, Germany, and the United States, with increasing contributions from developing economies. Thematic analysis indicates a shift from traditional strategy-oriented perspectives to more dynamic, digitally enabled, and sustainability-driven approaches. This study contributes to the literature by mapping the evolution of BMI as an interdisciplinary field and identifying future research opportunities, particularly in underexplored regions and application contexts.